2018
DOI: 10.1038/s41394-018-0076-5
|View full text |Cite
|
Sign up to set email alerts
|

International Spinal Cord Society (ISCoS) database: Asian Spinal Cord Network (ASCoN) Pilot Project [IDAPP]

Abstract: The study confirms that establishing the SCI database is possible using the variables, processes and web platform of the pilot study. It also provides a low cost solution. Expansion to other centers/regions and including non-traumatic SCI would be the next step forward.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…14,16e18 Lack of proper prehospitalization care, initial management by quacks, late presentation and poor transportation of injured patients to tertiary care hospitals, as prevalent in the region all account for high rates for complete injuries as reported in the IDAPP study also. 2 Cervical spine injuries were most commonly observed to translate to complete neurological deficit. However, our results were different from Mathur et al 14 and Agarwal et al 18 who reported Lumbar and Thoracolumbar injuries respectively to be the most common level for complete traumatic SCI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,16e18 Lack of proper prehospitalization care, initial management by quacks, late presentation and poor transportation of injured patients to tertiary care hospitals, as prevalent in the region all account for high rates for complete injuries as reported in the IDAPP study also. 2 Cervical spine injuries were most commonly observed to translate to complete neurological deficit. However, our results were different from Mathur et al 14 and Agarwal et al 18 who reported Lumbar and Thoracolumbar injuries respectively to be the most common level for complete traumatic SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal Cord Injury (SCI) is associated with permanent disability and decreased life expectancy especially in low and middle-income countries. 1,2 The etiology of spine trauma varies with country and the results of the epidemiological study from developed countries do not apply to developing countries. 3,4 Worldwide, the incidence of spine trauma lies between 10.4 and 83 million inhabitants per year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Data were recorded using a collection form provided by ISCoS as part of their pilot study within the Asian Spinal Cord Network (ASCoN) known as ISCoS Database ASCON Pilot Project (IDAPP). 15 The form was read out to patients and filled out by a healthcare professional using information provided by the patient and information from the patient’s clinical records. This study analysed a one-year cohort (September 2015–August 2016) extracted from the dataset.…”
Section: Methodsmentioning
confidence: 99%
“…In Bangladesh, spinal cord injuries (SCI) are commonly due to work-related accidents in young manual labourers [1][2][3][4][5], often with low socioeconomic backgrounds [6][7][8]. A similar pattern is seen across other low-and middleincome countries (LMIC) [9][10][11][12]. SCI causes hardship for those who are injured and often also for the families who are financially dependent on them [3,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%